Consensus recommendations on exploring effective solutions for the rising cost of diabetes. Issue 2 (April 2017) - Sadikot, Shaukat M.; Das, Ashok Kumar; Wilding, John; Siyan, Ali; Zargar, Abdul Hamid; Saboo, Banshi; Aravind, S.R.; Sosale, Bhavana; Kalra, Sanjay; Vijayakumar, G.; Manojan, K.K.; Maheshwari, Anuj; et al.
Abstract: Diabetes remains asymptomatic for a long period of time and its real burden gets noticed only once the complications set in. The number of individuals affected with the disease is also on the rise and more so in the low income countries. This scenario calls for urgent precautionary measures that need to be undertaken to equip ourselves to fight against this chronic disease. Individuals with financial constraints cannot afford to access even the basic treatment facilities and thus stands the most burdened. The International Diabetes Federation calls for 'Eyes on Diabetes' for the society to focus on early screening and early intervention. The rising cost of diabetes results from delayed and denied treatment. The panel discussion organized as a part of 4th Annual global diabetes convention of Jothydev's Professional Education Forum (JPEF, 2016) facilitated a platform to address diabetes as a serious health concern that needs to be given immediate priority by the policymakers as well as public and also to discuss about the feasible measures that will help achieve cost effective and affordable diabetes treatment. This was followed by in-depth literature search and finally a set of recommendations have been arrived at by the key opinion leaders to realize the dream of affordable diabetes care to all deserving individuals.